Biophysics at the edge of life and death: Radical control of apoptotic mechanisms - Hack, Samantha J.; Beane, Wendy S.; Tseng, Kelly Ai-Sun (Frontiers in Cell Death, 2023)
Recent studies have furthered our understanding of how dying and living cells interact in different physiological contexts, however the signaling that initiates and mediates apoptosis and apoptosis-induced proliferation are more complex than previously thought. One increasingly important area of study is the biophysical control of apoptosis. In addition to biochemical regulation, biophysical signals (including redox chemistry, bioelectric gradients, acoustic and magnetic stimuli) are also known yet understudied regulators of both cell death and apoptosis-induced proliferation. Mounting evidence suggests biophysical signals may be key targets for therapeutic interventions. This review highlights what is known about the role of biophysical signals in controlling cell death mechanisms during development, regeneration, and carcinogenesis. Since biophysical signals can be controlled spatiotemporally, bypassing the need for genetic manipulation, further investigation may lead to fine-tuned modulation of apoptotic pathways to direct desired therapeutic outcomes.